2009
DOI: 10.1037/a0013463
|View full text |Cite
|
Sign up to set email alerts
|

Stereotype threat reinterpreted as a regulatory mismatch.

Abstract: Research documents performance decrements resulting from the activation of a negative taskrelevant stereotype. We combine a number of strands of work to identify causes of stereotype threat in a way that allows us to reverse the effects and improve the performance of individuals with negative task-relevant stereotypes. We draw on prior work suggesting that negative stereotypes induce a prevention focus, and other research suggesting that people exhibit greater flexibility when their regulatory focus matches th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
118
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(130 citation statements)
references
References 95 publications
9
118
1
2
Order By: Relevance
“…Given that much of personality and social psychology is concerned with understanding the factors that improve individuals' successful performance (Bayer & Gollwitzer, 2007;Grimm, Markman, Maddox, & Baldwin, 2009;Oettingen, Mayer, Thorpe, Janetzke, & Lorenz, 2005;Vasquez & Buehler, 2007), researchers typically view the relative lack of effort in group settings as a negative, hence the term social loafing. In the present research, we assume that any observed levels of underperformance may depend on why individuals are pursuing a shared goal to begin with (perceived value vs. need for progress).…”
Section: Balancing Effortsmentioning
confidence: 99%
“…Given that much of personality and social psychology is concerned with understanding the factors that improve individuals' successful performance (Bayer & Gollwitzer, 2007;Grimm, Markman, Maddox, & Baldwin, 2009;Oettingen, Mayer, Thorpe, Janetzke, & Lorenz, 2005;Vasquez & Buehler, 2007), researchers typically view the relative lack of effort in group settings as a negative, hence the term social loafing. In the present research, we assume that any observed levels of underperformance may depend on why individuals are pursuing a shared goal to begin with (perceived value vs. need for progress).…”
Section: Balancing Effortsmentioning
confidence: 99%
“…Thus, it seems that most women were responding similarly to the threat manipulation. Because the threat instructions were reiterated before each block, it is possible that most or all women responded by increasing their caution and effort, emphasized accuracy over speed, and stayed with a serial search strategy that may have inhibited learning (18,19).…”
Section: Gender | Math | Visual Searchmentioning
confidence: 99%
“…Although due to limited research, little is known about the underlying mechanisms of stereotype lift, a number of underlying processes have been considered as the basis for stereotype threat, including decreased working memory (Schmader, Johns, & Forbes, 2008), prevention focus (US university students: Grimm, Markman, Maddox, & Baldwin, 2009), and performance expectancies (UK university students: Rosenthal, Crisp, & Suen, 2007). It is possible that geometric-based navigation relies on different underlying processes than landmark-based navigation, which map onto the different processes outlined as mechanisms underlying stereotype threat.…”
mentioning
confidence: 99%